Determinan Produksi dan Pengukuran Return to Scale Usahatani Padi Irigasi di Desa Sri Agung Kabupaten Tanjung Jabung Barat - Adistya, Adilla; Asmaida, Asmaida (Jurnal MeA (Media Agribisnis), 2025)
Rice is the main commodity supporting national food security, and therefore increasing the productivity of rice farming remains a strategic priority. An effective way to enhance productivity is through the implementation of an irrigation system that regulates water management.This study aims to identify the determinants of irrigated rice production, estimate the elasticity of production factors on output, and analyze the return to scale condition of irrigated rice farming. The research was conducted in Sri Agung Village with 30 irrigated rice farmers selected purposively as respondents. The analysis employed the Cobb-Douglass production function using the OLS method. The input variables simultaneously had a significant effect on rice production, with an R-squared value of 0.927. Partially, land area, seed, and KCl fertilizer significantly influence rice production. The Return to Scale value is greater than 1, indicating that irrigated rice farming in Sri Agung Village is in a condition of increasing return to scale. These findings suggest that rice farming management in Sri Agung Village has the potential to be improved through more efficient input allocation and the application of more effective cultivation practices.